'Crossing the Red Line?': The Air Staff, Sir Arthur Harris, and the Magdeburg Operation of 21/22 January 1944. (November 2020) - Worrall, Richard John
On 21/22 January 1944, RAF Bomber Command conducted an area-bombing attack on the city of Magdeburg. The outcome was hardly pleasing, marked by high losses and inaccurate bombing. However, most notable was the rancorous aftermath, in which a full-blown row would erupt between the Air Ministry and Bomber Command Headquarters. This stemmed from the Air Staff perceiving that Sir Arthur Harris had 'crossed a red line' in his non-cooperation with their bombing policy. But the truth was much less clear-cut, as this article will show. Nonetheless, the Magdeburg operation led to a new Directive on 28 January 1944, which would force Harris's cooperation in a combined Anglo-American assault against the German aircraft industry.